Electronic and optical properties of amorphous GaSe thin films - Siqueira, M. C.; Machado, K. D.; Serbena, J. P. M.; Hummelgen, I. A.; Stolf, S. F.; Azevedo, C. G. G. de [UNESP]; Silva, J. H. D. da [UNESP] (Springer, 2016)
The eletronic and optical properties of amorphous GaSe thin films produced by vacuum evaporation were investigated using X-ray photoemission spectroscopy (XPS) and transmittance spectroscopy techniques. XPS measurements allowed the determination of the valence band energy and showed the chemical bonding and the charge transfer between Se and Ga atoms. Transmittance measurements allowed the determination of the optical gap, refractive index and extinction coefficient in the low and high absorption regions. Using the Wemple and DiDomenico single oscillator model we also found the oscillator and the dispersive energies. From the valence band and optical gap energies, the conduction band was found and an energy level diagram for f-GaSe is proposed.